Use of mixed methods research in intervention studies to increase young people’s interest in STEM: A systematic methodological review - Fàbregues, Sergi; Sáinz, Milagros; Romano, María José; Escalante-Barrios, Elsa Lucia; Younas, Ahtisham; López-Pérez, Beatriz-Soledad (Frontiers in Psychology, 2023)
Mixed methods research intervention studies integrate quantitative evaluation approaches, such as randomized controlled trials and quasi-experimental designs, with qualitative research to evaluate the effectiveness, efficacy, or other results of an intervention or program. These types of studies, which have attracted growing attention in recent years, enhance the scope and rigor of the evaluation. While various frameworks that summarize the justifications for carrying out these types of studies and provide implementation guidance have been published in the last few years in the health sciences, we do not know whether such frameworks have been properly implemented in the social and educational sciences. To fill this gap in our understanding, this review examined the methodological features and reporting practices of mixed methods intervention studies aimed at increasing young people’s interest in STEM. A systematic search was carried out in APA PsycNET, ERIC, ProQuest, Scopus, and Web of Science, and a hand search in 20 journals. We included peer-reviewed English-language articles that reported intervention studies with a quantitative component measuring outcomes specific to increasing secondary school students' interest in STEM fields, a qualitative component conducted before, during, or after the quantitative component, and evidence of integration of both components. Qualitative content analysis and ideal-type analysis were used to synthesize the findings. We found 34 studies; the majority published in the last ten years. Several patterns of mixed methods application were described in these studies, illustrating the unique insights that can be gained by employing this methodology. The reporting quality of the included studies was generally adequate, especially regarding the justification for using a mixed methods intervention design and the integration of the quantitative and qualitative components. Nonetheless, a few reporting issues were observed, such as a lack of detail in the presentation of the mixed methods design, an inadequate description of the qualitative sampling and analysis techniques, and the absence of joint displays for representing integration. Authors must pay attention to these issues to ensure that the insights obtained by the use of mixed methods research are effectively communicated. This review was funded by the Spanish Ministry of Economy, Industry and Competitiveness.